Study of design issues in a prototype lower-limb prosthesis - proof-of-concept in a 3D printed model - Moreira, Augusto Gonçalves (2021)
Dissertação de Mestrado Integrado em Engenharia Biomédica Ramo de Biomateriais, Reabilitação e Biomecânica